A Scientific Assessment of Lekhaniya Mahakashaya -Review - Karveti, Rekha; Mishra, Shiromani; Malviya, Reeta; chalmela, Neha; chaudhary, Tarun (International Research Journal of Ayurveda & Yoga, 2021)
Sthaulya(obesity) is emerging problem in this globalizing era. We cannot ignore it because it can cause other diseases like diabetes, heart diseases, gastric disorders ,hypertension etc. Every person wants to look good, but people suffering from obesity suffer from inferiority complex due to this paucity.so we can say that Sthaulya affect both physical and mental health. years ago, Acharya Charak described important Mahakashayas for healing, one of them is the Lekhaniya Mahakashaya. It includes 10 drugs which mainly made with combination of vayu and Agni Mahabhuta.